When supply meets demand: Wage inequality in Portugal - Mário Centeno; Álvaro A. Novo (IZA Journal of European Labor Studies, 2014)
Wage inequality in Portugal has increased over the last thirty years, with two distinct periods. The period from 1984 to the mid-90s witnessed strong increases in both upper- and lower-tail inequality. A shortage of skills combined with skill-biased technological changes were at the core of this evolution. Since the mid-90s, lower-tail inequality has decreased, while upper-tail inequality has increased, but at a slower rate. A larger supply of skills and polarization of labor demand contribute to this evolution. Other developed economies share similar trends, but the Portuguese experience shows clearly the role of supply and demand factors in shaping the wage distribution.
Keywords: J3; D3; O3; 330; Inequality; Polarization; Supply; Demand